Electrode material, method for preparing the same, electrode sheet, and semi-solid battery
Patent Information
- Application Number
- CN202611137511.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]目前常规提升半固态电池饿高温安全性的技术路径主要集中于两个外部层面:一是在电解液中添加高温阻燃剂,如磷系和氟代溶剂;二是在隔膜表面涂覆耐热无机陶瓷涂层,(如Al2O3和SiO2;但这些方法都属于“被动防护”或“延缓”策略,旨在提高材料本身的分解温度或延缓热传递速率,无法在热失控临界点主动切断放热反应链,尤其在半固态电池经历180℃及以上的极端热滥用时,具体如下:
本发明的电极材料,加入第一响应单元,而第一响应单元能在所述电极材料中形成动态共价键交联网络,而动态共价键交联网络的形成促使电极活性材料和导电剂更加稳定地限制于交联网络中,提高了电极活性材料和导电剂的粘结稳定性,并且动态共价键交联网络具有自修复能力,有助于维持电极材料形成的层结构的微观结构的整体性和离子/电子通路,进而有利于防止电极材料形成的层结构的早期崩塌,并且形成的动态共价键交联网络在T1温度下断裂且ΔH>0,即在动态共价键交联网络在T1温度下断裂的过程为吸热反应,可实现部分热量的吸收,进而为电池管理系统介入争取了关键时间;配合所述第二响应单元为绝缘固液相变材料,以使所述第二响应单元在T2温度下可由固态转变为液态,T1>T2,即在温度继续升高至T2的状态下,第二响应单元则会由固态转变为液态,液态的第二响应单元在电极材料形成的层结构的毛细作用下迅速渗透至电极孔隙及颗粒间隙中并包裹活性物质颗粒,形成一层连续且绝缘的物理屏障,实现了剧烈且不可控的放热副反应的阻断,从而从根本上切断电化学反应路径,即主动切断放热反应链,实现了半固态电池热失控的“高温熔断”和“主动防护”。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to an electrode material and its preparation method, an electrode sheet, and a semi-solid-state battery. Background Technology
[0002] Balancing the energy density and safety performance of lithium-ion batteries has been a long-standing challenge for the industry. Semi-solid-state batteries, as a compromise solution with high engineering potential, have made progress in improving energy density and thermal stability to some extent by mixing or combining solid electrolyte materials into traditional liquid electrolytes. In safety tests, especially for thermal abuse, such as hot box tests, and for mechanical abuse, such as nail penetration tests, semi-solid-state batteries outperform traditional liquid batteries, but the problem has not yet been completely solved.
[0003] Currently, conventional technologies for improving the high-temperature safety of semi-solid-state batteries mainly focus on two external aspects: one is adding high-temperature flame retardants, such as phosphorus-based and fluorinated solvents, to the electrolyte; the other is coating the separator surface with heat-resistant inorganic ceramic coatings (such as Al2O3 and SiO2). However, these methods are all "passive protection" or "delay" strategies, aiming to increase the decomposition temperature of the material itself or slow down the heat transfer rate. They cannot actively cut off the exothermic reaction chain at the thermal runaway critical point, especially when semi-solid-state batteries are subjected to extreme thermal abuse at 180°C and above, as detailed below: Binder network failure: Currently used binders such as PVDF and SBR generally have glass transition temperatures or decomposition temperatures below 180°C. At this extreme temperature, the binder will soften, melt, or even decompose, causing the conductive network and mechanical structure between the electrode active material particles to collapse. Structural collapse not only causes the battery to fail instantly, but more fatally, it exposes a large amount of fresh and highly active electrode material surface. The active material in the exposed electrode material surface is prone to violent and uncontrollable exothermic side reactions with the residual liquid electrolyte or solid electrolyte interface, such as oxygen release from the positive electrode and electrolyte decomposition. At this time, no external flame retardant or ceramic coating can prevent this intrinsic reaction that occurs inside the electrode, ultimately leading to inevitable thermal runaway, such as fire and explosion. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide an electrode material, its preparation method, electrode sheet, and semi-solid battery that can block violent and uncontrollable exothermic side reactions, thereby actively cutting off the exothermic reaction chain and realizing "active protection" against thermal runaway of semi-solid batteries.
[0005] The objective of this invention is achieved through the following technical solution: An electrode material includes the following components: an electrode active material, a conductive agent, a first response unit, and a second response unit; The first response unit is a binder, and the first response unit is used to form a dynamic covalent cross-linked network in the electrode material, and the formed dynamic covalent cross-linked network breaks at temperature T1 and ΔH>0; The second response unit is an insulating solid-liquid phase change material, so that the second response unit can change from solid to liquid at temperature T2; Where T1 > T2.
[0006] In one embodiment, T1 is 80°C to 150°C.
[0007] In one embodiment, T2 is 150°C to 220°C.
[0008] In one embodiment, the amount of the first response unit added does not exceed 3.5 wt% of the total mass of the electrode material.
[0009] In one embodiment, the amount of the second response unit added is 0.5% to 5.0% of the total mass of the electrode material.
[0010] In one embodiment, the particle size of the second response unit is 0.5 μm to 10 μm.
[0011] In one embodiment, the electrode active material is a high-nickel ternary NCM material or a silicon-carbon composite anode material.
[0012] In one embodiment, the conductive agent is at least one of carbon black, carbon nanotubes, and graphene.
[0013] In one embodiment, the first responsive unit is a binder having a furan ring and maleimide groups.
[0014] In one embodiment, the second response unit is an inorganic eutectic salt.
[0015] In one embodiment, the second responsive unit is a thermoplastic polymer microsphere.
[0016] In one embodiment, the second response unit is a low-melting-point alloy microparticle.
[0017] In one embodiment, the first responsive unit is a polyamide-imide having a furan ring and maleimide groups.
[0018] In one embodiment, the first responsive unit is at least one of an acrylonitrile-butyl acrylate copolymer having furan rings and maleimide groups, a polyurethane elastomer having furan rings and maleimide groups, and a polyimide-epoxy hybrid resin having furan rings and maleimide groups.
[0019] In one embodiment, the second response unit includes LiNO3, NaNO3, and KNO3.
[0020] In one embodiment, the second response unit is a polyethylene wax microcapsule and / or a modified polycaprolactone microsphere.
[0021] In one embodiment, the second response unit is a Bi-In-Sn alloy.
[0022] A method for preparing an electrode material, used to prepare the electrode material described in any of the above embodiments, the method comprising the following steps: Obtain electrode active material, conductive agent, first response unit, and second response unit; The electrode active material, the conductive agent, the first response unit, and the second response unit are added to a solvent for homogeneous dispersion.
[0023] An electrode sheet includes a current collector, on at least one side of which the electrode material described in any of the above embodiments is attached, so that an electrode material layer is formed on the current collector.
[0024] In one embodiment, the porosity of the electrode material layer is 20% to 35%.
[0025] A semi-solid battery includes a semi-solid electrolyte and an electrode sheet as described in any of the above embodiments, wherein the electrode sheet is immersed in the semi-solid electrolyte.
[0026] In one embodiment, the semi-solid electrolyte is a phase change semi-solid composite electrolyte, and the semi-solid electrolyte undergoes a phase change at temperature T3; Where T3 < T1.
[0027] In one embodiment, T3 is 60°C to 70°C.
[0028] In one embodiment, the phase change semi-solid composite electrolyte is a VO2-doped vinyl oxide solid electrolyte, a VO2 and LLZO-doped polyethylene oxide solid electrolyte, a W and VO2-doped polyacrylonitrile solid electrolyte, or a mixed solid electrolyte containing VO2, LiPF5, EC, and EMC.
[0029] Compared with the prior art, the present invention has at least the following advantages: The electrode material of the present invention incorporates a first response unit, which forms a dynamic covalent cross-linked network within the electrode material. This dynamic covalent cross-linked network more stably confines the electrode active material and conductive agent within the cross-linked network, improving their bonding stability. Furthermore, the dynamic covalent cross-linked network possesses self-healing capabilities, helping to maintain the integrity of the microstructure and ion / electron pathways of the layered structure formed by the electrode material. This, in turn, helps prevent early collapse of the layered structure. Moreover, the formed dynamic covalent cross-linked network breaks at temperature T1 with ΔH > 0, meaning the process of breaking the dynamic covalent cross-linked network at temperature T1 is an endothermic reaction, thus realizing partial heat recovery. This absorption process buys crucial time for the battery management system to intervene. Furthermore, the second response unit is an insulating solid-liquid phase change material, allowing it to transition from solid to liquid at temperature T2. Since T1 > T2, if the temperature continues to rise to T2, the second response unit will change from solid to liquid. Under the capillary action of the layered structure formed by the electrode material, the liquid second response unit rapidly penetrates into the electrode pores and interparticle spaces, encapsulating the active material particles and forming a continuous and insulating physical barrier. This effectively blocks the violent and uncontrollable exothermic side reactions, fundamentally cutting off the electrochemical reaction pathway—that is, actively severing the exothermic reaction chain—and achieving "high-temperature melting" and "active protection" against thermal runaway in semi-solid-state batteries. Detailed Implementation
[0030] The present application will be further described in detail below with reference to the embodiments and examples. It should be understood that these embodiments and examples are for illustrative purposes only and are not intended to limit the scope of the present application. The purpose of providing these embodiments and examples is to enable a more thorough and comprehensive understanding of the disclosure of the present application. It should also be understood that the present application can be implemented in many different forms and is not limited to the embodiments and examples described herein. Those skilled in the art can make various modifications or alterations without departing from the spirit of the present application, and the equivalent forms obtained also fall within the protection scope of the present application. Furthermore, numerous specific details are set forth in the following description to provide a fuller understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0032] In this invention, the technical features described in an open-ended manner include both closed-ended technical solutions composed of the listed features and open-ended technical solutions that include the listed features.
[0033] In this invention, numerical intervals (i.e., numerical ranges) are involved. Unless otherwise specified, the selected numerical distributions within the aforementioned numerical intervals are considered continuous, and include the two endpoints (i.e., the minimum and maximum values) of the numerical range, as well as every value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints. In this document, this is equivalent to directly listing every integer. For example, if t is an integer selected from 1 to 10, it means that t is any integer selected from the group of integers consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10. Furthermore, when multiple ranges are provided to describe features or characteristics, these ranges can be merged. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges to which they are included.
[0034] Unless otherwise specified, the temperature parameters in this invention can be either constant temperature treatment or variations within a certain temperature range. It should be understood that the constant temperature treatment allows temperature fluctuations within the precision range controlled by the instrument. Fluctuations are permitted within ranges such as ±5℃, ±4℃, ±3℃, ±2℃, and ±1℃.
[0035] This application provides an electrode material. The electrode material comprises the following components: an electrode active material, a conductive agent, a first response unit, and a second response unit. The first response unit is a binder, and is used to form a dynamic covalent cross-linked network in the electrode material, wherein the formed dynamic covalent cross-linked network breaks at temperature T1 and ΔH > 0. The second response unit is an insulating solid-liquid phase change material, so that the second response unit can change from a solid to a liquid state at temperature T2. T1 > T2.
[0036] To better understand the electrode material of this application, the following further explanation is provided: One embodiment of the electrode material includes the following components: an electrode active material, a conductive agent, a first response unit, and a second response unit. The first response unit is a binder and is used to form a dynamic covalent cross-linked network in the electrode material, wherein the formed dynamic covalent cross-linked network breaks at temperature T1 and ΔH > 0. The second response unit is an insulating solid-liquid phase change material, allowing it to transition from a solid to a liquid state at temperature T2. T1 > T2.
[0037] The aforementioned electrode material, with the addition of a first response unit, forms a dynamic covalent cross-linked network within the electrode material. This dynamic covalent cross-linked network more stably confines the active electrode material and conductive agent within the network, improving their bonding stability. Furthermore, the dynamic covalent cross-linked network possesses self-healing capabilities, helping to maintain the integrity of the microstructure and ion / electron pathways of the layered structure formed by the electrode material. This, in turn, helps prevent early collapse of the layered structure. Moreover, the formed dynamic covalent cross-linked network breaks at temperature T1 with ΔH>0, meaning the process of breaking the dynamic covalent cross-linked network at temperature T1 is an endothermic reaction, allowing for partial heat absorption. This allows for crucial time for the battery management system to intervene. Furthermore, the second response unit is an insulating solid-liquid phase change material, enabling it to transition from solid to liquid at temperature T2. Since T1 > T2, if the temperature continues to rise to T2, the second response unit will transition from solid to liquid. Under the capillary action of the layered structure formed by the electrode material, the liquid second response unit rapidly penetrates into the electrode pores and interparticle spaces, encapsulating the active material particles and forming a continuous and insulating physical barrier. This effectively blocks the violent and uncontrollable exothermic side reactions, fundamentally cutting off the electrochemical reaction path—that is, actively severing the exothermic reaction chain—and achieving "high-temperature melting" and "active protection" against thermal runaway in semi-solid-state batteries.
[0038] In one embodiment, the electrode active material is either a positive electrode active material or a negative electrode active material. Further, the positive electrode active material is a high-nickel ternary NCM material. Further, the negative electrode active material is a silicon-carbon composite negative electrode material. It should be noted that the high-nickel ternary NCM material and the silicon-carbon composite negative electrode material are conventionally used positive or negative electrode active materials in semi-solid-state batteries; therefore, their specific compositions are not described in detail here. Further, the conductive agent is at least one of carbon black, carbon nanotubes, and graphene. Further, the carbon black is at least one of acetylene black, Ketjen black, and furnace black. Further, the carbon nanotubes are single-walled carbon nanotubes and / or multi-walled carbon nanotubes. Further, the conductive agent includes carbon black and carbon nanotubes. Further, the mass ratio of carbon black to carbon nanotubes is (2~5):1, to form a conductive network that accommodates both point and line contacts.
[0039] In one embodiment, T1 is 80°C to 150°C. Further, T2 is 150°C to 220°C. Further, T2 is 170°C to 210°C. Further, T2 is 175°C to 195°C. It is understandable that 80℃~150℃ is the acceleration period of thermal runaway in semi-solid-state batteries. This is the explosive stage of side reactions, such as the large-scale decomposition of the SEI film and electrolyte. During this stage, the first response unit promotes the formation of a dynamic covalent cross-linked network in the electrode material, mainly to reduce the severe collapse of the layer structure formed by the electrode material, thereby reducing the occurrence of side reactions. Secondly, it promotes the breakage of the formed dynamic covalent cross-linked network at temperature T1 and ΔH>0, which can achieve partial heat absorption, thus buying critical time for the battery management system to intervene. However, the occurrence of side reactions still exists. That is, the rate of temperature rise of the semi-solid-state battery is slowed down, and the overall temperature of the semi-solid-state battery is still rising. Combined with T2 being 150℃~220℃, preferably 160℃~220℃, the overall temperature of the semi-solid-state battery is still rising. 10℃, more preferably 175℃~195℃, and 150℃~220℃ are the critical period for thermal runaway of semi-solid batteries. At this time, the electrode material and electrolyte continue to decompose. If the temperature continues to rise, the semi-solid battery will face fire and explosion. At this stage, the second response unit is prompted to change from solid to liquid. The liquid second response unit is an insulating solid-liquid phase change material. At this time, the second response unit rapidly penetrates into the electrode pores and particle gaps through the capillary action of the layer structure formed by the electrode material and wraps the active material particles, forming a continuous and insulating physical barrier. This achieves the blocking of violent and uncontrollable exothermic side reactions, thereby fundamentally cutting off the electrochemical reaction path, that is, actively cutting off the exothermic reaction chain, and realizing the "high temperature melting" and "active protection" of the semi-solid battery thermal runaway.
[0040] It is understandable that if the second response unit is used directly without the first response unit, that is, if the second response unit is directly liquefied at temperature T2 and acts on the layered structure formed by the electrode material, the binder will soften, melt, or even decompose. This will cause the layered structure formed by the electrode material to "collapse" early when the semi-solid battery thermally runs away to below T2. That is, at temperatures below 150°C, the binder network in the layered structure formed by the electrode material in the semi-solid battery is prone to failure, leading to the collapse of the layered structure. Thus, at temperatures below 150°C in the semi-solid battery, the active material on the exposed surface of the electrode material caused by the collapse will undergo violent and uncontrollable release at the interface with the residual electrolyte. Thermal side reactions cause a rapid rise in the local temperature of the layered structure formed by the electrode material, which exacerbates local collapse. Even if the second response unit can liquefy when the temperature reaches T2, the structure of the layered structure formed by the electrode material changes after the binder softens, melts, or even decomposes. The second response unit, which cannot reach a liquid state, penetrates into the electrode pores and interparticle gaps under the capillary action of the layered structure formed by the electrode material and encapsulates the active material particles, forming a continuous and insulating physical barrier. This achieves the effect of blocking the violent and uncontrollable exothermic side reactions. In other words, using only the second response unit without using it in conjunction with the first response unit cannot achieve the effect of blocking the violent and uncontrollable exothermic side reactions.
[0041] In one embodiment, the amount of the first response unit added does not exceed 3.5 wt% of the total mass of the electrode material. Further, the amount of the first response unit added is 0.5 wt% to 3.5 wt% of the total mass of the electrode material. Further, the first response unit is a binder having a furan ring and maleimide groups.
[0042] In one embodiment, the first response unit is a polyamide-imide having a furan ring and maleimide groups. Further, the electrode material includes an electrode active material, a conductive agent, PVDF, the first response unit, and the second response unit. Further, the amount of the first response unit added is 0.5 wt% to 2.0 wt% of the total mass of the electrode material. Further, the total amount of the first response unit and PVDF added is 1.0 wt% to 3.5 wt%. Further, the electrode material includes the following components in parts by mass: 94.0 to 96.5 parts of electrode active material, 1.5 to 3.0 parts of conductive agent, 0.5 to 1.5 parts of PVDF, 0.5 to 2.0 parts of the first response unit, and 0.5 to 5.0 parts of the second response unit.
[0043] In one embodiment, the first responsive unit is at least one selected from the following: an acrylonitrile-butyl acrylate copolymer having furan rings and maleimide groups, a polyurethane elastomer having furan rings and maleimide groups, and a polyimide-epoxy hybrid resin having furan rings and maleimide groups. Further, the electrode material includes an electrode active material, a conductive agent, a first responsive unit, and a second responsive unit. Further, the amount of the first responsive unit added is 1.5 wt% to 3.5 wt% of the total mass of the electrode material. Further, the amount of the first responsive unit added is 2.0 wt% to 2.8 wt% of the total mass of the electrode material. Further, the electrode material includes the following components in parts by weight: 94.0 to 96.5 parts of electrode active material, 1.5 to 3.0 parts of conductive agent, 1 to 3.5 parts of the first responsive unit, and 0.5 to 5.0 parts of the second responsive unit.
[0044] In one embodiment, the amount of the second response unit added is 0.5% to 5.0% of the total mass of the electrode material. Further, the amount of the second response unit added is 1.0% to 3.0% of the total mass of the electrode material.
[0045] In one embodiment, the particle size of the second response unit is 0.5 μm to 10 μm.
[0046] In one embodiment, the second response unit undergoes an irreversible phase transition at temperature T2. It is understood that if the second response unit does not undergo a reversible phase transition at temperature T2, it is difficult to accurately match the thermal runaway trigger temperature, and the response speed to thermal runaway is relatively slow. However, ensuring that the second response unit does not undergo an irreversible phase transition at temperature T2 allows for accurate matching of the thermal runaway trigger temperature and improves the response speed to thermal runaway. It is also understood that if the temperature at which the solid-to-liquid transition of the second response unit is directly lowered, i.e., T2 is lowered to a temperature at which the binder does not soften, melt, or decompose, and if the solid-to-liquid transition occurs at T1, the semi-solid-state battery would undergo a phase transition at a relatively low temperature and become unusable. Conversely, if the second response unit is a material that undergoes a reversible phase transition directly from solid to liquid at T1, it is impossible to completely achieve "high-temperature melting" for thermal runaway in the semi-solid-state battery.
[0047] In one embodiment, the second response unit is an inorganic eutectic salt. Further, T2 is 175℃~195℃. Further, the second response unit includes LiNO3, NaNO3, and KNO3, which can rapidly absorb and release heat, has an extremely fast response speed, and exhibits good fluidity in the molten state. It easily penetrates rapidly into the electrode pores and particle gaps through the capillary action of the layered structure formed by the electrode material, encapsulating the active material particles and forming a continuous and insulating physical barrier, thus blocking the violent and uncontrollable exothermic side reactions. Further, the mass ratio of LiNO3, NaNO3, and KNO3 is (3~7):(3~7):(6~14). Further, the mass ratio of LiNO3, NaNO3, and KNO3 is (3~5):(3~5):(10~14). Further, the mass ratio of LiNO3, NaNO3, and KNO3 is (4~6):(4~6):(8~12). Further, the mass ratio of LiNO3, NaNO3, and KNO3 is (5~7):(5~7):(6~10). Further, the mass ratio of LiNO3, NaNO3, and KNO3 is 1:1:3, resulting in a phase transition temperature of approximately 175°C for the second response unit. Further, the mass ratio of LiNO3, NaNO3, and KNO3 is 1:1:2, resulting in a phase transition temperature of approximately 185°C for the second response unit. Further, the mass ratio of LiNO3, NaNO3, and KNO3 is 3:3:4, resulting in a phase transition temperature of approximately 195°C for the second response unit.
[0048] In one embodiment, the second response unit is a thermoplastic polymer microsphere. Further, the second response unit is a polyethylene wax microcapsule and / or modified polycaprolactone microsphere, which results in the second response unit having low viscosity in the molten state, good fluidity, and easy rapid penetration into the electrode pores and interparticle spaces through the capillary action of the layered structure formed by the electrode material, encapsulating the active material particles and forming a continuous and insulating physical barrier, thereby blocking the violent and uncontrollable exothermic side reactions. Further, the modified polycaprolactone microsphere is a PCL-PLA copolymer, which is a copolymer of ε-caprolactone and L-lactide. Further, the molar ratio of ε-caprolactone to L-lactide in the modified polycaprolactone microsphere is 1:(1~3). Further, the molar ratio of ε-caprolactone to L-lactide in the modified polycaprolactone microsphere is 1:1, resulting in a phase transition temperature of approximately 150°C for the second response unit. Further, the molar ratio of ε-caprolactone to L-lactide in the modified polycaprolactone microspheres is 1:2, resulting in a phase transition temperature of approximately 180°C for the second response unit. Further, the molar ratio of ε-caprolactone to L-lactide in the modified polycaprolactone microspheres is 1:3, resulting in a phase transition temperature of approximately 200°C for the second response unit. Further, the second response unit comprises polyethylene wax microcapsules and modified polycaprolactone microspheres. Further, in the second response unit, the mass ratio of polyethylene wax microcapsules to modified polycaprolactone microspheres is (0.5~2):(0.5~2). Further, the mass ratio of polyethylene wax microcapsules to modified polycaprolactone microspheres is 1:1.
[0049] In one embodiment, the second response unit is a low-melting-point alloy microparticle. Further, T2 is 150℃~210℃. Further, the second response unit is a Bi-In-Sn alloy, which allows the second response unit to have good fluidity in the molten state, easily penetrating rapidly into the electrode pores and particle gaps through the capillary action of the layered structure formed by the electrode material, and encapsulating the active material particles to form a continuous and insulating physical barrier, thereby blocking the violent and uncontrollable exothermic side reactions. Further, the mass ratio of Bi, In, and Sn is (10~13):(3~6):4. Further, the mass ratio of Bi, In, and Sn is (11~13):(3~5):4. Further, the mass ratio of Bi, In, and Sn is (12~13):(3~4):4. Further, the mass ratio of Bi, In, and Sn is (58~62):(18~22):(18~22). Furthermore, the mass ratio of Bi, In, and Sn is 5:3:2, resulting in a phase transition temperature of approximately 150°C for the second response unit. Further, the mass ratio of Bi, In, and Sn is 11:5:4, resulting in a phase transition temperature of approximately 170°C for the second response unit. Further, the mass ratio of Bi, In, and Sn is 3:1:1, resulting in a phase transition temperature of approximately 185°C for the second response unit. Further, the mass ratio of Bi, In, and Sn is 13:3:4, resulting in a phase transition temperature of approximately 210°C for the second response unit.
[0050] This application also provides a method for preparing an electrode material, used to prepare the electrode material described in any of the above embodiments. One embodiment of the electrode material preparation method includes the following steps: S100: Obtain electrode active material, conductive agent, first response unit and second response unit; S200: The electrode active material, the conductive agent, the first response unit and the second response unit are added to a solvent for homogeneous dispersion.
[0051] The above-described method for preparing electrode materials effectively achieves the dispersion of the electrode materials.
[0052] It is understood that polyamide-imides with furan rings and maleimide groups have a main chain containing aromatic polyamide-imide segments, while the side chains or end groups are formed by introducing furan rings and maleimide groups through a chemical medium. Furthermore, the grafting rate (molar ratio) of polyamide-imides with furan rings and maleimide groups is 5% to 15%.
[0053] In one embodiment, the preparation of a polyamide-imide having a furan ring and a maleimide group comprises the following steps: dissolving furan-isocyanate in anhydrous tetrahydrofuran, adding an equimolar amount of tert-butyloxycarbonyl (Boc) anhydride, and stirring the reaction at room temperature for 4 hours to obtain Boc-protected furan-isocyanate; dissolving maleimide-isocyanate in anhydrous tetrahydrofuran, adding an equimolar amount of tert-butyloxycarbonyl anhydride, and stirring the reaction at room temperature for 4 hours to obtain Boc-protected maleimide-isocyanate; and further dissolving maleimide-isocyanate in anhydrous tetrahydrofuran, adding an equimolar amount of tert-butyloxycarbonyl anhydride, and stirring the reaction at room temperature for 4 hours to obtain Boc-protected maleimide-isocyanate. A polyamide-imide precursor containing hydroxyl or amino groups (number average molecular weight 20,000-50,000) is dissolved in N-methylpyrrolidone to prepare a 10 wt% solution. Then, Boc-protected furan-isocyanate and Boc-protected maleimide-isocyanate are added separately, and the mixture is stirred at 60°C for 24 h. Next, trifluoroacetic acid (5% of the solution volume) is added, and the mixture is stirred at 40°C for another 2 h to remove the Boc protecting groups. After the reaction is complete, the entire mixture is poured into methanol to precipitate, filtered, washed, and dried under vacuum. Further, the molar ratio of furan ring to maleimide group in the polyamide-imide containing furan ring and maleimide group is (0.8~1.2):(0.8~1.2). Further, the molar ratio of furan ring to maleimide group in the polyamide-imide containing furan ring and maleimide group is 1:1. Further, in another embodiment, the preparation of polyamide-imide having a furan ring and maleimide groups includes the following steps: furan-2,5-diamine and N-(4-aminophenyl)maleimide are dissolved in anhydrous N-methylpyrrolidone to prepare a 20 wt% solution, which is placed in a three-necked flask under nitrogen protection; PMDA is added in three batches, with each batch spaced 30 min apart, while maintaining an ice-water bath at 0-5°C during the addition process; after the addition is complete, stirring is continued for 2 h to obtain a polyamic acid (PAA) precursor solution; the above PAA solution is heated to 180°C and stirred for 6 h under nitrogen protection to carry out a thermal imidization cyclization reaction to obtain the target polymer. 4. After the reaction is complete, the solution is cooled to room temperature, poured into methanol to precipitate, filtered, washed, and dried under vacuum at 150°C for 12 h. Further, the molar ratio of furan-2,5-diamine and N-(4-aminophenyl)maleimide is 1:1. Furthermore, the molar amount of pyromellitic dianhydride (PMDA) is equal to the total molar amount of furan-2,5-diamine and N-(4-aminophenyl)maleimide.
[0054] It is understood that the acrylonitrile-butyl acrylate copolymer with furan rings and maleimide groups has a main chain formed by the polymerization reaction of acrylonitrile and butyl acrylate, while the side chains or end groups are formed by introducing furan rings and maleimide groups through a chemical medium. Acrylonitrile enables the acrylonitrile-butyl acrylate copolymer with furan rings and maleimide groups to have good adhesion, while butyl acrylate ensures that the acrylonitrile-butyl acrylate copolymer with furan rings and maleimide groups has good flexibility. Further, in one embodiment, the acrylonitrile-butyl acrylate copolymer with furan rings and maleimide groups is obtained by the following steps: dissolving acrylonitrile, butyl acrylate, furan-methacrylate and maleimide-methacrylate in DMF in a molar ratio of 6:2:1:1, adding AIBN initiator, polymerizing at 70°C for 12 h, precipitating and drying.
[0055] It is understandable that polyurethane elastomers with furan rings and maleimide groups have a main chain consisting of polyether polyol soft segments and diisocyanate hard segments, while the side chains or end groups are furan rings and maleimide groups introduced through chemical media. The diisocyanate hard segments enable polyurethane elastomers with furan rings and maleimide groups to have good adhesion, while the polyether polyol soft segments ensure that polyurethane elastomers with furan rings and maleimide groups have good flexibility. Further, the preparation of polyurethane elastomers with furan rings and maleimide groups includes the following steps: polytetrahydrofuran (PTMG, number average molecular weight 2000) is added to a reaction flask, dehydrated under vacuum at 120°C for 2 hours, cooled to 80°C, and isophorone diisocyanate (IPDI) and dibutyltin dilaurate (0.05% of the total monomer mass) are added. The mixture is stirred at 80°C for 3 hours to obtain an isocyanate-terminated prepolymer. Furan-2,5-dimethylamine and N-(2-aminoethyl)maleimide are dissolved in N,N-dimethylformamide and slowly added dropwise to the isocyanate-terminated prepolymer. The dropwise addition time is controlled at 30 minutes. After the dropwise addition is completed, the reaction is continued at 60°C for 6 hours. After the reaction is completed, a small amount of methanol is added to terminate the residual isocyanate, and then the mixture is poured into deionized water to precipitate. The precipitate is filtered and dried under vacuum at 50°C for 24 hours. Furthermore, the molar ratio of polytetrahydrofuran: isophorone diisocyanate: furan-2,5-dimethylamine: N-(2-aminoethyl)maleimide is 1:2.2:0.6:0.6.
[0056] It is understandable that polyimide-epoxy hybrid resins with furan rings and maleimide groups have a main chain of polyimide containing epoxy groups, while the side chains or end groups are furan rings and maleimide groups introduced through chemical media. The polyimide containing epoxy groups enables polyimide-epoxy hybrid resins with furan rings and maleimide groups to have good adhesion and strength. Further, the preparation of a polyimide-epoxy hybrid resin having a furan ring and maleimide groups includes the following steps: dissolving bisphenol A dianhydride (BPADA) and m-phenylenediamine (m-PDA) in NMP and reacting at 0℃-5℃ for 4 h to form polyamic acid; then adding glycidol (glycidyl ether) and heating to 180℃ for thermal imidization for 6 h to obtain a polyimide with epoxy groups at the end of the polymer chain; dissolving the polyimide with epoxy groups at the end of the polymer chain in dimethyl sulfoxide (10 wt%), adding furan-carboxylic acid and maleimide-carboxylic acid, and a catalyst triphenylphosphine (1% of the total mass of carboxylic acid), and stirring at 120℃ for 12 h to allow the carboxylic acid and epoxy groups to undergo a ring-opening esterification reaction. Further, the molar ratio of BPADA, m-PDA, and glycidol is 1 : 0.8 : 0.2. Further, the epoxy value (molar number of epoxy groups per 100g of resin) of the polyimide with epoxy groups located at the end of the polymer chain is controlled at 0.05-0.10 mol / 100g. Further, the molar ratio of furan-carboxylic acid and maleimide-carboxylic acid is 1:1, and the total amount of furan-carboxylic acid and maleimide-carboxylic acid is equal to the molar amount of epoxy groups. Further, the grafting rate (molar ratio) of the polyimide-epoxy hybrid resin having furan rings and maleimide groups is ≥5%-15%. Further, the molar ratio of furan groups to maleimide groups in the polyimide-epoxy hybrid resin having furan rings and maleimide groups is (0.8~1.2):(0.8~1.2). Furthermore, in the polyimide-epoxy hybrid resin having furan rings and maleimide groups, the molar ratio of furan groups to maleimide groups is 1:1.
[0057] In one embodiment, the inorganic eutectic salt is obtained by mixing LiNO3, NaNO3 and KNO3 in a certain proportion.
[0058] In one embodiment, the Bi-In-Sn alloy is obtained by alloying Bi, In and Sn monomers according to a specific ratio.
[0059] In one embodiment, the modified polycaprolactone microspheres are obtained by the following steps: under nitrogen protection, ε-caprolactone and L-lactide are mixed, stannous octoate (catalyst, amount of which is 0.1% of the total mass of monomers) is added, and the mixture is reacted at 120°C for 24 h. The product is dissolved in dichloromethane, precipitated in methanol, dried under vacuum, and then spray-granulated to obtain modified polycaprolactone microspheres with a D50 of 3-8 μm.
[0060] This application also provides an electrode sheet. One embodiment of the electrode sheet includes a current collector, on at least one side of which the electrode material described in any of the above embodiments is attached, so that an electrode material layer is formed on the current collector.
[0061] In one embodiment, the porosity of the electrode material layer is 20% to 35%.
[0062] In one embodiment, after the electrode material is coated onto the current collector, it is dried and then left to stand at a temperature of 100°C to 120°C for 1 to 2 hours to form a dynamic covalent cross-linked network. Further, it is dried at a temperature of 80°C for 30 minutes.
[0063] This application also provides a semi-solid battery, one embodiment of which includes a semi-solid electrolyte and an electrode sheet as described in any of the above embodiments, wherein the electrode sheet is immersed in the semi-solid electrolyte.
[0064] In one embodiment, the semi-solid electrolyte is a phase change semi-solid composite electrolyte, and the semi-solid electrolyte undergoes a phase change at a temperature T3; wherein, T3 < T1.
[0065] In one embodiment, T3 is 60°C to 70°C. Further, T3 is 68°C.
[0066] In one embodiment, the phase change semi-solid composite electrolyte is a VO2-doped polyethylene oxide solid electrolyte, a VO2 and LLZO (lithium lanthanum zirconium oxide)-doped polyethylene oxide solid electrolyte, a W (tungsten) and VO2-doped polyacrylonitrile solid electrolyte, or a mixed solid electrolyte containing VO2, LiPF5, EC, and EMC. This allows the phase change semi-solid composite electrolyte to undergo phase change at lower temperatures, thereby increasing internal resistance and suppressing current. This addresses electrical abuse in the mid-temperature range. In conjunction with the first and second phase change units, it achieves stepwise thermal runaway protection from low to medium to high temperatures, specifically from current suppression to reactant cutoff.
[0067] Compared with the prior art, the present invention has at least the following advantages: The electrode material of the present invention incorporates a first response unit, which forms a dynamic covalent cross-linked network within the electrode material. This dynamic covalent cross-linked network more stably confines the electrode active material and conductive agent within the cross-linked network, improving their bonding stability. Furthermore, the dynamic covalent cross-linked network possesses self-healing capabilities, helping to maintain the integrity of the microstructure and ion / electron pathways of the layered structure formed by the electrode material. This, in turn, helps prevent early collapse of the layered structure. Moreover, the formed dynamic covalent cross-linked network breaks at temperature T1 with ΔH > 0, meaning the process of breaking the dynamic covalent cross-linked network at temperature T1 is an endothermic reaction, thus realizing partial heat recovery. This absorption process buys crucial time for the battery management system to intervene. Furthermore, the second response unit is an insulating solid-liquid phase change material, allowing it to transition from solid to liquid at temperature T2. Since T1 > T2, if the temperature continues to rise to T2, the second response unit will change from solid to liquid. Under the capillary action of the layered structure formed by the electrode material, the liquid second response unit rapidly penetrates into the electrode pores and interparticle spaces, encapsulating the active material particles and forming a continuous and insulating physical barrier. This effectively blocks the violent and uncontrollable exothermic side reactions, fundamentally cutting off the electrochemical reaction pathway—that is, actively severing the exothermic reaction chain—and achieving "high-temperature melting" and "active protection" against thermal runaway in semi-solid-state batteries.
[0068] The embodiments of this application will be described in detail below with reference to examples. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application. For experimental methods in the following embodiments where specific conditions are not specified, please refer to the guidelines given in this application, or follow experimental manuals or conventional conditions in the art, or follow the conditions recommended by the manufacturer, or refer to experimental methods known in the art.
[0069] In the specific embodiments described below, the measurement parameters involving raw material components may have slight deviations within the weighing accuracy range unless otherwise specified. For temperature and time parameters, acceptable deviations due to instrument testing accuracy or operational precision are permissible.
[0070] It should be understood that in the various embodiments of this application, the order of the above-mentioned processes does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.
[0071] Example 1
[0072] Table 1: Raw materials for electrode materials
[0073] Raw materials for the electrode materials of each embodiment and comparative example as shown in Table 1 were obtained respectively; The electrode active material, the conductive agent, the first response unit, and the second response unit were added to NMP to make the solid content 65%, and dispersed at 800 rpm for 2 hours. Then, the remaining NMP was added to adjust the solid content to 60%, and the dispersion was continued for 1 hour to obtain the electrode slurry corresponding to Examples 1-1 to 29 and Comparative Example 1.
[0074] Example 2
[0075] 1. Preparation of positive electrode sheet Electrode paste coating and drying: The electrode pastes of each group obtained in Example 1 were coated on 12μm aluminum foil, with a wet film thickness of 150μm, dried at 80℃ for 30min, and then vacuum dried at 120℃ for 2h. Roll pressing: Roll pressing was performed until the compaction density was 3.4 g / cm3 and the porosity was 25±2%, to obtain the positive electrode sheets corresponding to Examples 1-1~29 and Comparative Example 1, respectively; 2. Preparation of negative electrode sheet (conventional process, without adding functional components) Raw materials: graphite (D50=15μm), Super P, SBR, CMC Formula: Graphite : Super P : SBR : CMC = 95.5 : 1.5 : 1.5 : 1.5 Preparation: Aqueous slurry is coated onto 8μm copper foil, dried, and rolled.
[0076] 3. Preparation of semi-solid electrolytes Raw materials: VO2 nanoparticles (D50=50nm), PEO (Mv=600k), LiTFSI Formula: VO2: PEO: LiTFSI = 20: 60: 20 (mass ratio) Preparation: Dissolved in acetonitrile, with a solid content of 10%, cast into a PTFE mold and dried at 50℃ for 48h to obtain a 50μm thick electrolyte membrane.
[0077] 4. Battery Assembly Structure: Positive electrode | Solid electrolyte membrane | Electrode sheet Assembly: The negative electrode and solid electrolyte membrane are encapsulated with the positive and negative electrode sheets of each group using aluminum-plastic film, and hot-pressed at 80°C (0.5 MPa, 10 min) to ensure good interface contact.
[0078] Formation: Charged to 4.2V at a constant current of 0.05C and left to stand at 45℃ for 24 hours to obtain the batteries corresponding to Examples 1-1 to 29 and Comparative Example 1, respectively.
[0079] The following tests were performed on the batteries corresponding to Examples 1-1 to 29 and Comparative Example 1: Experimental objective: To verify the "high-temperature melting" and "active protection" effects of the batteries corresponding to Examples 1-1 to 29 and Comparative Example 1 in a 180°C hot box test.
[0080] Test conditions: Test standard: Refer to GB / T 31485-2015 Hot Box Test Method Sample status: 100% SOC fully charged Temperature program: Increase temperature to 180℃ at a rate of 5℃ / min, then maintain the temperature. Monitoring parameters: battery surface temperature, open circuit voltage, insulation resistance The experimental results are shown in Table 2: Table 2:
[0081] Data Interpretation: The batteries obtained in Examples 1-1 to 29 stabilized after their surface temperature rose to ≥190°C in a 180°C hot box without a rapid temperature rise. Furthermore, the battery voltage rapidly dropped to 0V when the temperature reached ~180°C, indicating that the electrochemical reaction had been cut off and the fuse was effective. Upon disassembly, a uniform coating layer was observed on the surface of the positive electrode, encapsulating the active material particles. The insulation resistance test value was >50MΩ, and even reached >100MΩ, proving that the ion / electron pathway was effectively blocked. This verified the "high-temperature fuse" function under extreme thermal abuse conditions at 180°C, achieving active protection against thermal runaway.
[0082] The embodiments described above are merely illustrative of several implementation methods of this application, intended to facilitate a detailed understanding of the technical solutions of this application, but should not be construed as limiting the scope of protection of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the scope of protection of this application. Furthermore, it should be understood that after reading the above teachings of this application, those skilled in the art can make various alterations or modifications to this application, and the equivalent forms obtained also fall within the scope of protection of this application. It should also be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided in this application through logical analysis, reasoning, or limited experimentation are all within the scope of protection of the appended claims. Therefore, the scope of protection of this patent application should be determined by the content of the appended claims, and the specification can be used to interpret the content of the claims.
Claims
1. An electrode material, characterized in that, It includes the following components: electrode active material, conductive agent, first response unit and second response unit; The first response unit is a binder, and the first response unit is used to form a dynamic covalent cross-linked network in the electrode material, and the formed dynamic covalent cross-linked network breaks at temperature T1 and ΔH>0; The second response unit is an insulating solid-liquid phase change material, so that the second response unit can change from solid to liquid at temperature T2; Where T1 > T2.
2. The electrode material according to claim 1, characterized in that, The T1 is 80℃~150℃; and / or, The T2 is 150℃~220℃; and / or, The amount of the first response unit added does not exceed 3.5 wt% of the total mass of the electrode material; and / or, The amount of the second response unit added is 0.5% to 5.0% of the total mass of the electrode material; and / or, The particle size of the second response unit is 0.5 μm to 10 μm; and / or, The electrode active material is a high-nickel ternary NCM material or a silicon-carbon composite anode material; and / or... The conductive agent is at least one selected from carbon black, carbon nanotubes, and graphene; and / or, The first responsive unit is a binder having a furan ring and maleimide groups; and / or, The second response unit is an inorganic eutectic salt; and / or, The second responsive unit is a thermoplastic polymer microsphere; and / or, The second response unit is a low-melting-point alloy microparticle.
3. The electrode material according to claim 1, characterized in that, The first responsive unit is a polyamide-imide having a furan ring and maleimide groups; and / or, The first responsive unit is at least one of an acrylonitrile-butyl acrylate copolymer having furan rings and maleimide groups, a polyurethane elastomer having furan rings and maleimide groups, and a polyimide-epoxy hybrid resin having furan rings and maleimide groups.
4. The electrode material according to claim 1, characterized in that, The second response unit includes LiNO3, NaNO3, and KNO3; and / or, The second responsive unit is a polyethylene wax microcapsule and / or a modified polycaprolactone microsphere; and / or, The second response unit is a Bi-In-Sn alloy.
5. A method for preparing an electrode material, used to prepare the electrode material according to any one of claims 1 to 4, characterized in that, The preparation method of the electrode material includes the following steps: Obtain electrode active material, conductive agent, first response unit, and second response unit; The electrode active material, the conductive agent, the first response unit, and the second response unit are added to a solvent for homogeneous dispersion.
6. An electrode sheet, characterized in that, The current collector includes an electrode material as described in any one of claims 1 to 5, which is attached to at least one side surface of the current collector to form an electrode material layer on the current collector.
7. The electrode sheet according to claim 6, characterized in that, The porosity of the electrode material layer is 20%~35%.
8. A semi-solid-state battery, characterized in that, It includes a semi-solid electrolyte and the electrode sheet of claim 7, wherein the electrode sheet is immersed in the semi-solid electrolyte.
9. The semi-solid-state battery according to claim 8, characterized in that, The semi-solid electrolyte is a phase change semi-solid composite electrolyte, and the semi-solid electrolyte undergoes a phase change at temperature T3; Where T3 < T1.
10. The semi-solid-state battery according to claim 9, characterized in that, The T3 is 60℃~70℃; and / or, The phase change semi-solid composite electrolyte is a VO2-doped vinyl oxide solid electrolyte, a VO2 and LLZO-doped polyethylene oxide solid electrolyte, a W and VO2-doped polyacrylonitrile solid electrolyte, or a mixed solid electrolyte containing VO2, LiPF5, EC, and EMC.